Determinan Faktor-Faktor yang Mempengaruhi Capaian Standar Pelayanan Minimal Kesehatan - Giyanti, Fitri; Priyadi, Unggul (ARBITRASE: Journal of Economics and Accounting, 2026)
Public policy in the health sector plays an important role in ensuring the fulfillment of basic services for the community through the implementation of Minimum Service Standards (SPM) for Health. The achievement of SPM for Health is an indicator of the performance of local governments in carrying out their mandatory duties in the health sector. Although the SPM policy has been implemented nationally, the achievement of SPM for Health at the community health center (Puskesmas) level still shows variations between regions. This study aims to analyze the factors that influence the achievement of the Minimum Health Service Standards in Gunungkidul Regency for the period 2020–2024 from the perspective of performance-based public policy. The study used a quantitative approach with panel data from 30 Puskesmas over five years. The independent variables included human resources, facilities, medical equipment, medicines, service targets, and budget, while the dependent variable was the achievement of the Minimum Service Standards for Health. The analysis was conducted using panel data regression with the Fixed Effect model as the best model. The results of the study indicate that simultaneously, all variables have a significant effect on the achievement of Health SPM. Partially, facilities, medical equipment, service targets, and budget have a significant effect, while human resources and medicines do not have a significant effect. The results of the budget efficiency analysis show that the highest realization of BOK funds was at the Ponjong I Community Health Center, amounting to Rp796,207,009, and the lowest was at Ngawen I, amounting to Rp369,157,623, while the highest SPM achievement was achieved by the Patuk II Community Health Center (82.44%) and the lowest was by Semin II (71.84%). These findings confirm that the effectiveness of Health SPM policies is largely determined by infrastructure support and performance-based public budget management.